PENYELESAIAN PELAKSANAAN PERJANJIAN KREDIT PEMBIAYAAN MULTIGUNA AKIBAT NASABAH MENINGGAL DUNIA - Muhamad Zanuar Prasetyo (MIMBAR YUSTITIA, 2021)
Financial institutions provide consumer financing facilities (multipurpose financing) in the form of funding for consumer needs (customers) to purchase consumptive needs. The agreement process for the consumer financing facility must be able to convince the financing company. However, if the consumer (debtor) dies, who is still bound by the obligation to pay the installments, it is necessary to settle the implementation of the credit agreement. This study uses a normative legal research method by discussing the problem of goods credit agreements with multipurpose financing facilities on the completion of the implementation of multipurpose financing credit agreements caused by the customer's death. In connection with the death of the debtor, if the circumstances of death are the same as default in the form of not fulfilling any achievements at all, then the obligations of the deceased debtor must be continued by the person who is the guarantor in the financing agreement (in this case it can be the wife/husband or other person who his name is called the guarantor in the financing agreement).